Transcriptional regulation of human UDP-glucuronosyltransferase genes - Hu, Dong Gui; Meech, Robyn; McKinnon, Ross A.; Mackenzie, Peter I. (Drug metabolism reviews, 2014)
Abstract Glucuronidation is an important metabolic pathway for many small endogenous and exogenous lipophilic compounds, including bilirubin, steroid hormones, bile acids, carcinogens and therapeutic drugs. Glucuronidation is primarily catalyzed by the UDP-glucuronosyltransferase (UGT) 1A and two subfamilies, including nine functional UGT1A enzymes (1A1, 1A3-1A10) and 10 functional UGT2 enzymes (2A1, 2A2, 2A3, 2B4, 2B7, 2B10, 2B11, 2B15, 2B17 and 2B28). Most UGTs are expressed in the liver and this expression relates to the major role of hepatic glucuronidation in systemic clearance of toxic lipophilic compounds. Hepatic glucuronidation activity protects the body from chemical insults and governs the therapeutic efficacy of drugs that are inactivated by UGTs. UGT mRNAs have also been detected in over 20 extrahepatic tissues with a unique complement of UGT mRNAs seen in almost every tissue. This extrahepatic glucuronidation activity helps to maintain homeostasis and hence regulates biological activity of endogenous molecules that are primarily inactivated by UGTs. Deciphering the molecular mechanisms underlying tissue-specific UGT expression has been the subject of a large number of studies over the last two decades. These studies have shown that the constitutive and inducible expression of UGTs is primarily regulated by tissue-specific and ligand-activated transcription factors (TFs) via their binding to cis-regulatory elements (CREs) in UGT promoters and enhancers. This review first briefly summarizes published UGT gene transcriptional studies and the experimental models and tools utilized in these studies, and then describes in detail the TFs and their respective CREs that have been identified in the promoters and/or enhancers of individual UGT genes.